Advances in hydrogen generation through aluminum-assisted water split reaction - E. Czech (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
Hydrogen generated through aluminum-assisted water split reaction is a novel, efficient and environmentally friendly method. It has been found previously that the passivation of aluminum can be prevented in neutral (pH=7) or near neutral pH conditions in water by grinding aluminum with a catalyst, such as A12O3, SiO2 or SiC. Recently, the best results have been obtained by using water-soluble inorganic salts (WIS), ground with aluminum. The massive, rapid corrosion reaction of the Al-WIS system which takes place in regular tap (or marine, or ground) water can be utilized to produce hydrogen by aluminum-assisted water split reaction, in-situ, on-demand. The reaction offers clean, low-cost, environmentally benign and entirely recyclable technology for on-board on-demand hydrogen generation. Besides pure gaseous hydrogen, only pure solid aluminum hydroxides AlOOH or Al(OH)3 are formed as the reaction products. The hydrogen yield and Al-WIS reaction efficiency are high. From 1 g of mechanically alloyed aluminum powder, up to 1.25 liters of hydrogen were generated, i.e. efficiency up to 92% was achieved. The amount of hydrogen and hydrogen generation rate depend on various reaction parameters. The effect of chemistry and concentration of additives, water temperature, powder particle size and milling conditions on the reaction kinetics will be presented and the possible process mechanism will be discussed.